The Effects Of Mathematical Discussion Environment Supported By Metacognitive Problems On The Problem Posing Skills Of 3Th Grade Primary School Grade Students - Pusat Pilten; Isik, Necip; M. Koray Serin (Zenodo, 2017)
The aim of this research is to examine the effects of mathematical discussion envıronment supported by metacognitive problems on the problem posing skills of grade 3th primary school grade students. The study was carried out based on pre-test and post-test, control group model. Two experiment and one control group were formed from the students who participated in the research. The sample group consists of 52 students who are studying at the third grade level. According to the findings obtained from the research, it is seen that the discussion method supported by metacognitive questions applied in experiment-1 group, is especially effective in the dimensions of problem posing as “Realization of the Components of the Problem (RCP)”, “Identification of the relationship between concept and operation (IRCC)”, “Establishment of the problem requiring desired operation (EPRDO)” and “Posing problems based on the given visual and numerical data (PPGVN)”.
Keywords: problem-solving; primary grades; metacognition; discussion; 4. Education; 3. Good health